I Could Drone On and On About This Title - McCorkendale, Kole; Bhattarai, Ganesh P.; McCornack, Brian (My University, 2017)
The objective of this experiment was to test if an aerial survey system could be more effective and efficient than a ground survey performed by a human. We did this by detecting markers set in a field. Effectiveness is defined as how many markers/targets are found. Efficiency is compared by using time it took to record the data. At the end of the experiment, we found the aerial survey method was better than the ground survey in both aspects. This suggests there is a potential future for using drones to survey fields.